Cardiorespiratory dynamics to hypoxia at the onset of cycling exercise in male endurance subjects - Perrey, S.; Cleuziou, C.; Lecoq, A. M.; Courteix, D.; Obert, P. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: It is well established that altering O2 delivering to contracting skeletal muscle affects human performance. In this respect, a reduced O2 supply (e.g., hypoxia) increases the rate of muscle fatigue. This study aimed to determine the effects of moderate hypoxia and exercise intensity on oxygen uptake (V.O2) and cardiac output (CO) kinetics during moderate [below the ventilatory threshold (VT)] and heavy (above VT) constant work rate cycling exercises. Methods: Eight trained males (age, mean±SD, 22±3 years; height 182±5 cm; body mass 71±12 kg) performed at the same relative intensity in normoxic (FIO2=0.21) and hypoxic (FIO2=0.13) conditions moderate and heavy exercises during which pulmonary gas exchange was determined breath-by-breath and CO was monitored beat-by-beat with Doppler echocardiography. Results: The rate of increase (t63%, corresponding to time constant and time delay of a monoexponential response) in CO was significantly faster than that of V.O2 in 3 out of 4 experimental conditions (p<0.05). Moreover V.O2 kinetics were significantly slowed by hypoxia and speeded by exercise intensity, while CO responses were unaffected by such conditions. A slowed CO response was apparent in hypoxia compared to normoxia (p>0.05) in heavy exercise. Conclusion: These results suggest an absence of coupling between CO and V.O2 kinetics, and that cardiorespiratory O2 delivery is likely different at exercise onset as a function of exercise intensity and FIO2.